Sistem Informasi Akuntansi Persediaan Barang Habis Pakai Di Politeknik Jambi - Rezagi Meilano; Emanuel Chandra (LP2M Politeknik Jambi, 2020)
Inventory accounting information system is the main and most important information system in carrying out the activities of calculating an inventory in an organization, this research is intended as the development of an inventory accounting information system that aims to facilitate users in processing inventory accounting data. This study aims to analyze the information system of consumable inventory at Jambi Polytechnic. In this research, data collection techniques used include interviews, and literature studies. From the results of the analysis that has been done at the Jambi Polytechnic, it has used an information system, but it is still not effective in the management of consumables. This can be seen from the merging of one information system to process various data assets, inventory, and inventory of consumable goods themselves, and the program system used is inadequate to make reports of consumable inventory by utilizing the theory of inventory accounting standards. The development method is carried out using the System Development Life Cycle method and the Waterfall model which is a development model tends not to change. Based on the results of the study, the authors developed an inventory accounting information system that can be accessed by users so as to facilitate data processing and minimize the use of time and output reports in the form of inventory cards with the First In First Out and Last In First Out methods as the basis for using inventory accounting theory.